The Depiction and Interpretation of the Ambiguous Nature of Boredom and Everyday Life in Contemporary Comics (KULT_online, 2017)
With What Happens When Nothing Happens Greice Schneider lays the groundwork for an aesthetics of boredom and everyday life in comics by steadily exploring and travelling between the concepts of comics, boredom, and narratology. The author sets important constraints on comics storytelling in relationship to boredom by drawing on works of contemporary comic scholars. Moreover, the book historically traces the development of the concept of boredom, pointing out that there is no universally accepted definition of boredom. The term has been applied in many cultural contexts and covers a variety of states of mind. The book furthermore offers tools to analyse boredom in contemporary comics, since boredom is not yet a narratological concept.